Newly discovered Planetary Nebulae population in Andromeda (M31): PN Luminosity function and implications for the late stages of stellar evolution. Issue Volume 14:Issue S343(2019) (August 2018) - Bhattacharya, Souradeep; Arnaboldi, Magda; Hartke, Johanna; Gerhard, Ortwin; Comte, Valentin; McConnachie, Alan; Harris, William E.
Abstract: Stars with masses between ∼0.7 and 8 M⊙ end their lives as Planetary Nebulae (PNe). With the MegaCam at CFHT, we have carried out a survey of the central 16 sq. degrees of Andromeda (M31) reaching the outer disk and halo, using a narrow-band [OIII]5007 and a broad-band g filter. This survey extends previous PN samples both in uniform area coverage and depth. We identify ∼4000 PNe in M31, of which ∼3000 are new discoveries. We detect PNe down to ∼6 mag below the bright cut-off of the PN luminosity function (PNLF), ∼2 mag deeper than in previous works. We detect a steep rise in the number of PNe at ∼4.5 mag fainter than the bright cut-off. It persists as we go radially outwards and is steeper than that seen in the Magellanic clouds. We explore possible reasons for this rise, which give insights into the stellar population of M31.